E-HRYVNIA AS A STEP TOWARDS REFORMS IN THE FINANCIAL SYSTEM OF UKRAINE: FOREIGN EXPERIENCE - Ustinova, Irina (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
The purpose of the study is to analyze the foreign experience of introducing national electronic currency and their legal regulation and to try to express a position on the mechanisms for protecting the rights of individuals when introducing new payment instruments by Ukrainian legislation in the process of introducing electronic money. Research methods: the article uses the following general scientific research methods: observation and description, and theoretical methods: analysis, generalization, explanation, as well as systemic, functional, and specific sociological methods. Results: the author outlines modern world approaches to the introduction of electronic money arising from the objective grounds for the development of the financial system and financial control and virtual assets; identifies and formulates the main trends in the context of determining the processes of protecting the rights of persons involved in such legal relations. Discussion: recently, there have been rapid developments in digital technologies, which undoubtedly affects the development of the financial system, in particular. The role of innovations is growing, new payment technologies and services are appearing in the financial market, and central banks are considering the possibility of introducing their own digital currency. Undoubtedly, the launch of the e-hryvnia will be a significant step for Ukraine in shaping its image as a modern high-tech country, as it will be one of the first examples of the introduction of a new instrument for regulating monetary circulation at the state level. The introduction of the e-hryvnia will also strengthen the integration of the national digital currency with other government electronic services. The concept of a central bank digital currency has been around for several years. With the launch of digital money, countries around the world have set high expectations related to improving financial inclusion, promoting economic growth, creating a secure digital payment system, and making financial transactions transparent.